2018
DOI: 10.1021/acs.cgd.8b00819
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Tetranuclear Copper(I) Iodide Metal–Organic Cluster [Cu4I4(Ligand)5] with Highly Selective Luminescence Detection of Antibiotic

Abstract: Antibiotics in wastewater are very harmful to the environment and human health; their effective detection is important but still challenging. Herein, the first copper­(I) iodine-based antibiotic sensor [Cu4I4­(EBT)5] (denoted as UJN-Cu, EBT = 3-ethyl-1,3-benzothiazole-2-thione) was prepared through a facile solvothermal synthesis method and structurally determined by single crystal X-ray diffraction. The molecular structure of UJN-Cu adopts a chair-like structure of [Cu4I4­(Ligand)5], which is distinctly diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 59 publications
4
19
0
Order By: Relevance
“…This strong emission is ascribed to the charge transfer triplet excited state between Cu and the ligand, which is consistent with previous relevant mechanism studies of the copper iodine cluster. 84 From the sensing experiments, it was found that the prepared LMOF has the maximum luminescence quenching efficiency toward TCH with a quick response (Fig. 6b).…”
Section: Copper Iodide Cluster-based Lmofsmentioning
confidence: 94%
See 2 more Smart Citations
“…This strong emission is ascribed to the charge transfer triplet excited state between Cu and the ligand, which is consistent with previous relevant mechanism studies of the copper iodine cluster. 84 From the sensing experiments, it was found that the prepared LMOF has the maximum luminescence quenching efficiency toward TCH with a quick response (Fig. 6b).…”
Section: Copper Iodide Cluster-based Lmofsmentioning
confidence: 94%
“…83 Recently, two Cu x I y -based LMOFs have been reported as luminescence sensors for monitoring antibiotics. 84,85 In 2018, G. Liu et al synthesized a novel chair-like [Cu 4 I 4 ] cluster-based LMOF, [Cu 4 I 4 (EBT) 5 ] (UJN-Cu, EBT = 3-ethyl-1,3benzothiazole-2-thione) (Fig. 5a).…”
Section: Copper Iodide Cluster-based Lmofsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coordination chemistry is an important branch of chemistry and is involved many active research fields (Mirza et al, 2018;Liu et al, 2018aLiu et al, , 2019cYamamura et al, 2010;Wang et al, 2012;Duan et al, 2019;Zhang et al, 2020b;Cao et al, 2017). In salen-based ligands [R-CH N-(CH 2 ) n -N CH-R] and their corresponding homometallic and heterometallic complexes, due to their potential application values, intense research in modern coordination chemistry is still ongoing (Bhanja et al, 2020;Maity et al, 2020;Bag et al, 2020;Song et al, 2018;Majumdar et al, 2018;Zhang et al, 2015;Wang et al, 2009;Lo Presti et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…To solve these problems, crystalline hybrid copper­(I) iodine clusters formed by copper­(I) iodine cores and coordinated ligands drew intense attention due to their photoactive functions as well as the abundant, nontoxic, and relatively low-cost Cu element. Also, these clusters show promising applications in the fields of photochemistry and photophysics, for instance, stimuli-responsive luminescence and solid-state lighting. , As a result, they are promising candidates for potential application in environmental contamination optical detection, despite currently remaining less explored . Herein, we report the function synergistic strategy to construct a stable hybrid copper iodine cluster-based optical sensor.…”
Section: Introductionmentioning
confidence: 99%